Performance indicators in measuring academic library. - Sahak, Mohd Dasuki; Omar, Zoharah
The aim of this review paper is to explore the library performance indicator in the academic library. In the year of 2011, Malaysian Academic Library had decided to use British Standard International Organization for Standardization (ISO) 11620: 2008, Library performance indicators as a standard to measure library performance. Key Performance Indicators (KPls) is defined as simple and effective measurement system that helps organization to explain and manage the service progress for customer, aligned with the vision and mission of the organization. A review of research articles will examine the theoretical framework, types of measures and performance indicators, studied by several authors. The indicators will be categorized into five areas of measurement, based on the British Standard categories. The categories are resources, access, infrastructure, use, efficiency, and lastly potentials and development. The findings of this study will become as an added value for the librarians to know what are the indicators and areas of measurement that are mostly used to measure the library effectiveness and how it can help to develop KPls to be more practical, appropriate, informative and with valid measures.